A processual view on grammar: macrogrammar and the final field in spoken syntax. (March 2016) - Haselow, Alexander
Abstract: This paper presents an approach to linguistic analysis that distinguishes two cognitive serialization principles according to which speakers build up a unit of talk in real-time speech production, microgrammar and macrogrammar, and thus two different "category pools" from which speakers choose constituents. Based on empirical data of spontaneous spoken English, it will be argued that macrogrammatical elements serve different cognitive tasks that arise at particular points in the linear production of an utterance, such as fine-tuning epistemic value or modifying illocutionary force. This article focuses on one particular temporal slot for the production of macrogrammatical units, the potential end of a unit of talk or "final field", providing an analysis of different unit types available for use in this slot and discussing the basic cognitive tasks these units serve in conversational interaction. Highlights: Spontaneous speech is rich in morphosyntactically unintegrated elements. Two serialization principles are distinguished: microgrammar and macrogrammar. Macrogrammar captures elements outside morphosyntactic dependency relations. The end of a unit of talk (final field) is a crucial point in speech production. Elements in the final field serve a specific set of cognitive tasks.